Exploring Liver Cancer Treatment Strategies from Multiple Dimensions of Liver Physiology in the Yellow Emperor’s Classic of Internal Medicine - Gong, Xianrun; Zhang, Yami (Journal of Contemporary Medical Practice, 2026)
Primary liver cancer is a disease that seriously endangers human health, with high incidence and mortality rates, making its prevention and treatment a global challenge. In traditional Chinese medicine, it is classified under categories such as “hypochondriac pain” and “accumulation”. The Yellow Emperor’s Classic of Internal Medicine provides a comprehensive understanding of the physiological attributes of the liver. The liver governs dispersion and regulates qi movement; abnormalities can lead to qi stagnation, blood stasis, and phlegm accumulation; the liver stores blood, regulates blood volume, and controls blood; the liver is yin in nature but uses yang, and maintaining a balance between yin and yang is crucial; the liver has a close relationship with other organs. Based on this, treatment strategies for liver cancer include preventing disease before it occurs, emphasizing prevention before disease onset; strengthening the body’s vital energy and expelling pathogenic factors, such as nourishing qi, strengthening the spleen, nourishing the liver and kidneys, nourishing yin to promote fluid production and strengthen the body’s vital energy, promoting blood circulation to remove blood stasis, clearing heat and detoxifying, softening hard masses and resolving nodules to expel pathogenic factors; regulating emotions; and adhering to a holistic approach and syndrome differentiation. Integrating traditional Chinese and Western medicine can enhance treatment efficacy.